Biodiversity of microorganisms in the duodenum of broiler chickens under the influence of short-chain fatty acids and monoglycerides - L. M. Tamchuk; D. M. Masiuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The clear understanding of the taxa composition of the intestinal bacterial community will allow beneficial manipulation of the gut flora to improve gut health and broiler productivity. However, the integrative impact of short chain fatty acids and monoglycerides (SCFA-M) on the microbiota biodiversity of the duodenum in broiler chickens has been overlooked by researchers, which underpins the relevance of our study. The study was conducted on Cobb 500 broiler chickens under industrial poultry farm conditions. The broilers in the experimental group were given the IP. Enterin C3 – C10 formulation (in a dose of 1.5 L/30 L of 1 % water) supplemented via drinking water. PCR results revealed only genetic material related to Escherichia coli in the duodenum of the broiler chickens. No evidence for colonization of Clostridium perfringens or other microorganisms from the Eimeria sp. family were found. The bacterial presence of Eimeria acervulina in the duodenum was established on 27 and 34 days of life, that is evidence of the coccidiosis progression in the poultry. In 29-day-old broilers in the control group, the extent of duodenal colonization by E. acervulina was 67 % with an intensity of 2.17×105 ± 3.21×104 g-e. The extent of colonization was the similar for both 29-th and 36-th days of life. However, the intensity of colonization was decreased to 1.41×107 ± 8.48×106 g-e.  level. The extent of colonization decreased to 33% as well as the intensity decline was equal 3.37×105 g-e. The supplementation of SCFA-M induced the extent of duodenal colonization by E. acervulina about 17% decline in 29-day-old broilers in the experimental group. However, the rate of colonization intensity was significantly higher and equal 9.6×106 ± 4.7×105 g-e. The extent of colonization was increased to 100%, while the colonization intensity growth was rise to 2.9×108 ± 1.5×107 g-e. Contrary, there was no observed the genetic material of E. acervulina in the experimental group on 45-th day of life. Obtained data evidence that C3 – C10 formulation can be applied to manipulate microbiome community. Future research prospects include developing a SCFA-M administration scheme for broiler chickens to replace or minimize the use of antibacterial drugs in poultry farming.